2008
DOI: 10.1007/s10278-008-9115-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiologist Use of and Perceived Need for Patient Data Access

Abstract: Given the increasing volume of radiological exams, the decreasing frequency of direct communication with the referring provider, and the distribution of patient data over many clinical systems, radiologists often do not have adequate clinical information at the time of interpretation. We have performed a survey of radiologists to determine the need and actual utilization of patient data at the time of image interpretation. Our findings demonstrate that most radiologists want more clinical information when inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 2 publications
1
40
0
1
Order By: Relevance
“…The referenced study reports positive short-term effects on the information content of the CHI, but also observed that in a 3-month window, the "rates decayed back toward baseline." Several studies also showed positive impact of CPOE on the quality of clinical indications as compared to paper-based orders [12][13][14][15]. Technological innovation that automatically synthesizes patient background information and presents it to the radiologist in an intuitive manner is yet another route for resolving the clinical information communication gap between referring clinicians and radiologists laid bare by our study [16].…”
Section: Correlation Between Chi and Chrsupporting
confidence: 51%
See 1 more Smart Citation
“…The referenced study reports positive short-term effects on the information content of the CHI, but also observed that in a 3-month window, the "rates decayed back toward baseline." Several studies also showed positive impact of CPOE on the quality of clinical indications as compared to paper-based orders [12][13][14][15]. Technological innovation that automatically synthesizes patient background information and presents it to the radiologist in an intuitive manner is yet another route for resolving the clinical information communication gap between referring clinicians and radiologists laid bare by our study [16].…”
Section: Correlation Between Chi and Chrsupporting
confidence: 51%
“…In yet another study, less than 7 % of the clinical order indications were marked as reasonable or excellent [13]. A survey of radiologists showed that the majority (72 %) felt in need of more clinical information about their patients, and 87 % stated that additional information would have significant impact on interpretation [14].…”
Section: Correlation Between Chi and Chrmentioning
confidence: 96%
“…However, researchers involved in such work are cautioned that the problems with the present Radiology IT architecture run far deeper than can possibly be outlined in a single paper. To mention a few of these issues, environments with multiple RIS and PACS [16] installations add complexity, radiologists demand more extensive and relevant information about patients during interpretation [17], and sharing PACS among disparate institutions [18].…”
Section: Alternative Solutionsmentioning
confidence: 99%
“…2 Contrary to this, a recent systematic review showed that the provision of clinical information improved the diagnostic accuracy of reports without introducing bias. 3 Other studies have demonstrated that the provision of inadequate clinical information is more likely to result in an inaccurate report, whereas detailed clinical information increases the likelihood of the report being clinically relevant. 4 These effects are likely to be more significant for complex imaging studies such as temporal bone CT, where previous surgery can mimic disease processes and vice versa (e.g.…”
Section: Introductionmentioning
confidence: 98%